Upaya Peningkatan Berbahasa Inggris Para Pedagang di Pesisir Pantai Pulau Putri Karawang - Linny Anggani; Tatik Yuniarti; Saepudin Saepudin (Universitas Persada Indonesia YAI, 2023)
English plays an important role in every aspect of human life, one of which is the aspect oftourism which is oriented towards foreign tourists. For this reason, an effort to improve foreignlanguage skills is needed. This service program focuses on increasing motivation in speaking Englishand the confidence of merchant on the coast of Pulau Putri when communicating with foreign tourists.This activity consists of learning about (1) basic English conversation. (2) Directions to confusedtourists. (3) Bargaining communication. At the end of the session, merchant were asked to demonstratethe skills they had acquired after teaching. After this activity took place, it can be seen that 80% of themerchant who sell on the coast of Pulau Putri understand the importance of English for them andincrease their motivation to learn more so that local tourism is more advanced. This is because touristareas have the potential for foreign tourist destination. This success factor occurs through carefulprogram planning, the accuracy of materials and learning methods that are fun, participatory and theavailability of learning support tools.